1990
DOI: 10.1007/bf02390663
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of progesterone receptor in formalin-fixed and paraffin-embedded breast cancer tissue using a monoclonal antibody

Abstract: The potential for immunohistochemical detection of progesterone receptors (PRs) in routinely formalin-fixed and paraffin-embedded cancer tissues by use of the monoclonal antibody Mi 60-10 (mPR1, Dianova GmbH, Hamburg) was evaluated. The PR content of breast cancer tissue was investigated in 170 cases. A positive reaction to Mi 60-10 was found exclusively in the nuclei of benign or malignant epithelial cells. The distribution of PRs was heterogeneous. Immunohistochemical reaction was scored by multiplying the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Then, immunohistochemistry (IHC) staining was performed in 85 different-grade chondrosarcoma specimens to assess the expression level of TCF-1. A total of 25 % of tumor samples were positive [23] for TCF-1 staining. The results showed that TCF-1 expression level was higher in DDCS than in CCS, especially in the dedifferentiated portion of DDCS.…”
Section: Resultsmentioning
confidence: 99%
“…Then, immunohistochemistry (IHC) staining was performed in 85 different-grade chondrosarcoma specimens to assess the expression level of TCF-1. A total of 25 % of tumor samples were positive [23] for TCF-1 staining. The results showed that TCF-1 expression level was higher in DDCS than in CCS, especially in the dedifferentiated portion of DDCS.…”
Section: Resultsmentioning
confidence: 99%
“…The sections were probed with primary antibodies through the night at 4°C and the signal was developed with EnVision detection kit from DAKO. Immunostaining labeling intensities were defined as the number and the staining degree of positive cells:+less than 10% of the cells were positive and positive weakly; ++10%–50% of the cells were positive and positive medium, +++50–80% of the cells were positive and strong positive, ++++more than 80% cells were positive[34].The primary antibodies used in this study include anti-glypican-3(1∶500,ABBIOTEC),anti-MT(1∶50,DAKO), anti-Nrf2(1∶100,Abcam)…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical staining of cells for β-catenin and AXIN2 was scored according to stain intensity and extent of cells stained by semi-quantitative evaluation [16]. Brown-yellow staining observed mainly in cell plasma and cell nucleus was considered positive for β-catenin and AXIN2 protein expression.…”
Section: Methodsmentioning
confidence: 99%